Insulin-induced Oedema in a Patient with Diabetes Mellitus Complicated by Ketoacidosis - Alphonsus N. Onyiriuka; Frances A Ehirim (Acta Medica Indonesiana)
In this article we reported a recent case of a 15-year-old grossly underweight (29kg) Nigerian girl diagnosed of type 1 diabetes mellitus four years ago and who defaulted from follow up but presented with diabetic ketoacidosis. Glycaemic control was poor because of poor compliance. On the 5th day on admission, a non tender pitting oedema without skin discolouration developed over the ankles. The natural history of insulin-induced oedema was observed in this patient since the oedema resolved seven days later without any specific therapy, such as administration of diuretics. The major causes of generalized oedema in childhood and adolescence, such as kwashiorkor, nephrotic syndrome, liver cirrhosis, congestive heart failure and acute glumerulonephritis were excluded by findings from the history, physical examination and relevant laboratory investigations. Having excluded these major causes of oedema, the obvious conclusion was that the insulin therapy was the cause of the oedema observed in our patient. The aim of this article is to review existing medical literature on the subject of insulin-induced oedema and raise the awareness of clinicians on the subject. In conclusion, insulin-induced oedema should be considered in the differential diagnosis of oedema in children and adolescents with type 1 diabetes mellitus complicated by ketoacidosis, particularly if they are underweight.